2002
DOI: 10.1159/000067810
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme and Malondialdehyde Levels in Patients with Panic Disorder

Abstract: There is evidence of an etiopathogenetic role of free radicals (FRs) in some neuropsychiatric disorders. The aim of the present study was to determine whether the activity levels of some antioxidant enzymes [glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT)] and malondialdehyde (MDA), a product of lipid peroxidation, were associated with panic disorder (PD). Twenty patients diagnosed with PD and 20 healthy controls were enrolled in this study. A clinical evaluation and measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
4
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 15 publications
4
89
4
4
Order By: Relevance
“…These have reported elevated lipid peroxidation products and antioxidant changes in obsessive-compulsive disorder (Ersan et al, 2006;Kuloglu et al, 2002a), panic disorder (Kuloglu et al, 2002b) and social phobia (Atmaca et al, 2004), but not in post-traumatic stress disorder (Tezcan et al, 2003). The study on social phobia also found a reversal of these disturbances following 8 wk of citalopram treatment (Atmaca et al, 2004).…”
Section: Human Studiesmentioning
confidence: 99%
“…These have reported elevated lipid peroxidation products and antioxidant changes in obsessive-compulsive disorder (Ersan et al, 2006;Kuloglu et al, 2002a), panic disorder (Kuloglu et al, 2002b) and social phobia (Atmaca et al, 2004), but not in post-traumatic stress disorder (Tezcan et al, 2003). The study on social phobia also found a reversal of these disturbances following 8 wk of citalopram treatment (Atmaca et al, 2004).…”
Section: Human Studiesmentioning
confidence: 99%
“…ROS have been implicated as mediators of tissue damage in patients with rheumatoid arthritis. The synovial fluid of the inflamed rheumatoid joint swarms with activated neutrophils, which produce large amounts of ROS 2 . ROS are formed in oxidative processes that normally occur at relatively low levels in all cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Stressinduced alterations in the concentration of neurotransmitters such as excitatory amino acids, serotonin and gamma-amino-butyric acid can modulate the immune response and vice versa, and cytokines, mediators produced by immune cells, maintain homeostasis by communicating with other biological systems such as the hypothalamic-pituitary-adrenal (HPA) axis. 21,22 Recently, Kuloglu et al 23,24 recognized a link between oxidative stress and some anxiety disorders (obsessive-compulsive and panic disorder), demonstrating that oxidative metabolism can influence anxiety regulation. Bouayed et al 25 in their review summarized data which demonstrate a link between oxidative stress and anxiety, but an unambiguous cause-effect relationship has yet to be determined.…”
mentioning
confidence: 99%